On the convexity of phase-field fracture formulations: Analytical study and comparison of various degradation functions. (April 2023) - Svolos, Lampros; Plohr, JeeYeon N.; Manzini, Gianmarco; Mourad, Hashem M.
Abstract: Efficient and accurate fracture modeling is of great importance in applications where catastrophic outcomes under extreme scenarios are possible. The phase-field (PF) approach to fracture received significant attention over the past decade, due to its capability to capture complicated fracture patterns (e.g., crack merging and branching). Specifically, crack initiation and propagation are modeled via minimization of the total energy functional, which is regularized with the aid of a phase field. Despite the promising results and modeling capabilities of the PF method in many applications, the solution of fracture problems remains computationally challenging mainly due to the non-convexity of the total energy functional with respect to the combined unknown (phase field and displacement) fields. Understanding the effects of their coupling on convexity is crucial in order to address frequently encountered hurdles in fracture modeling (e.g., inefficient solvers and non-physical crack nucleation). In this paper, we develop convexity criteria for a wide class of PF fracture formulations. For this class of formulations, the second variation of the total energy functional is expressed in terms of Hessian matrices (evaluated at individual material points). Depending on the choice of geometric crack functions and degradation functions, we classify the formulations into three categories and analytically study each one separately. To study the sign of the second variation, we derive inequalities which are satisfied at material points when the Hessian matrix is locally positive semi-definite. These inequalities provide objective criteria for comparing degradation functions. The applicability of the proposed convexity criteria is demonstrated in the context of a one-dimensional problem, solved using a conventional monolithic solver. Highlights: We develop convexity criteria for a wide class of phase-field fracture formulations. Convexity and stability are related through the second variation of total energy. Objective criteria are derived by imposing a positive semi-definite Hessian matrix. Depending on degradation functions, criteria show different qualitative behavior. Non-convexity affects the numerical convergence of conventional monolithic solvers.